EARLY WARNING INDICATORS OF THE GLOBAL FINANCIAL CRISIS : Focus on bank profitability and funding in the United States 2004-2008 - Naski, Leena (My University, 2020)
The global financial crisis began in the United States in 2007, when the housing prices collapsed. Depositary and financial institutions noticed that the values of mortgage-backed securities in their balance sheets were dramatically less than expected. The banks’ profitability started to decrease severely. As the risks increased, the short-term liquidity dried up, and the trust in the collateral securities weakened. The institutions had to resort to more complex funding options. The complex structures of financial instruments and, excessive securitization spread the crisis to the whole banking system. This caused a panic, which paralyzed the efficient functioning of the financial markets. Private and public institutions tend to actively forecast and predict forthcoming crises and early warning indicators, that are sensitive to market changes vulnerabilities and by using econometric models. During the pre-crisis years in the U.S., the early warning indicators and early warning models failed to predict the beginning of the global financial crisis. The purpose of this study is to analyze, whether the beginning of the financial crisis could have been predicted with securitized short-term funding of the banking sector. The goal is to assess, if the volume of mortgage-backed securities, repurchase agreements and federal funds had a significant correlation and impact with bank profitability and return on equity. The question is whether these variables acted as early warning indicators. The data is from Worldscope-database and includes U.S. banks from 2004-2008. The empirical methods are linear multiple regression analysis and fixed-effects -regression analysis. Generally, in the academic literature, the studied variables have seen to be a direct impact and effect to the causes of the global financial crisis. However, the results of this study are divergent. The linear regression model only finds a significant positive correlation between the repurchase agreements and return on equity. This implies, that using repurchase agreements as early warning indicators is applicable only, if there is a noticeable large collapse or decrease in the volume of the agreements. On the contrary, the fixed-effects mode does not find any significant correlations with any of the variables. The interpretation is, that the unique bank-specific time-invariant characteristics and effects were the real fundamental reasons and causes for the severity and the start of the crisis. Equally, the underlying risks of the securities had a significant impact on the start of the crisis and the collapse of bank profitability. Based on the results, the studied variables do not act on their own as good reliable early warning indicators, and in the econometric early warning models, the time-invariant underlying unique characteristics and risks should strongly be accounted for. By doing this, crisis early warning prediction based on bank securities would obtain more efficient and usable prediction models and forecasts.

Globaali finanssikriisi sai alkunsa Yhdysvalloissa 2007 asuntomarkkinoiden hintojen romahtaessa. Rahoituslaitokset huomasivat taseissaan oleviensa asuntolainavakuudellisten arvopapereiden arvojen olevan nopeasti huomattavasti oletettua alhaisempia. Pankkien kannattavuus kääntyi jyrkkään laskuun. Lyhytaikainen likviditeetti ehtyi riskien kasvaessa ja luottamus arvopaperien vakuuksiin heikkeni. Rahoituslaitokset joutuivat turvautumaan mon-imuotoisempiin rahoitusratkaisuihin. Rahoitusinstrumenttien monimutkaiset rakenteet ja liiallinen arvopaperistaminen levittivät kriisin nopeasti koko pankkijärjestelmään. Tämä aiheutti paniikin, joka lamautti rahoitusmarkkinoiden tehokkaan toiminnan. Yksityiset ja julkiset instituutiot pyrkivät aktiivisesti ennustamaan ja ennakoimaan tulevia kriisejä ja markkinoiden muutoksille herkkiä ennakoivia indikaattoreita käyttämällä ekonometrisia mallinnuk-sia. Ennen finanssikriisiä Yhdysvalloissa ennakoivat indikaattorit ja mallinnukset kuitenkin epäonnistuivat ennustamaan kriisin alun. Tämän tutkimuksen tarkoituksena on analysoida, mikäli finanssikriisin alku olisi voitu ennakoida pankkijärjestelmän arvopaperistettujen ja lyhytaikaisen rahoituksen avulla. Päämääränä on selvittää, oliko asuntolainavakuudellisilla arvopapereilla, takaisinostosopimuksilla sekä yhdysvaltain keskuspankin liikkeellelaskemien pankkien välisten markkinoiden arvopapereilla merkittävä vaikutus pankkien kannattavuuteen ja pääoman tuottoasteeseen. Tärkeänä kysymyksenä on, toimivatko kyseiset muuttujat kriisejä ennakoivina indikaattoreina. Tutkimuksen aineisto sisältää Worldscope -tietokannan yhdysvaltalaisia pankkeja vuosilta 2004-2008. Tutkimusmenetelminä ovat lineaarinen sekä kiinteiden menetelmien -regressiomalli. Yleisesti kyseisillä muuttujilla on akateemisessa kirjallisuudessa nähty olevan suora vaikutus finanssikriisin alkuun. Tämän tutkimuksen tulokset ovat kuitenkin poikkeavia. Lineaarinen regressiomalli löytää ainoastaan merkittävän positiivisen korrelaation takaisinostosopimusten ja pankkien pääoman tuottoasteen väliltä. Tämä viittaa siihen, että takasisinostosopimusten käyttö ennakoivina indikaattoreina on soveltuvaa vain, jos sopimukset kärsivät nopeasta määrän laskusta tai romahduksesta. Kiinteiden menetelmien -malli puolestaan ei löydä minkäänlaisia merkittäviä korrelaatioita. Tässä tulkintana on, että pankkikohtaiset ajassa muuttumattomat taustalla olevat ominaisuudet olivat todelliset perusteelliset syyt kriisin vakavuudelle. Vastaavasti myös arvopapereiden taustalla olevat riskit vaikuttivat merkittävästi kriisin syntyyn ja pankkien kannattavuuden romahdukseen. Tulosten perusteella tutkitut muuttujat eivät itsessään toimi hyvinä ennakoivina indikaattoreina, ja käytetyissä ekonometrisissa malleissa tulisi vahvasti huomioida taustalla olevat muuttumattomat ominaisuudet ja riskit. Tällöin kriisien ennakoiminen pankkien arvopapereiden pohjalta tuottaisi tehokkaampia ja käyttökelpoisisempia ennusteita.
Keywords: banks (monetary institutions); financial crises; monetary policy; economic indicators; securitisation; regression analysis; profitability; lending; fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|